Constructing opposition in the age of globalization: the potential of ATTAC - Birchfield, Vicki; Freyberg-Inan, Annette (Globalizations, 2004)
This article examines the movement ATTAC and assesses its potential to function as a vital part of the emerging global opposition to neoliberal globalization. We analyze the agenda of the movement and assess its coherence, both in terms of policy evaluations and prescriptions and in terms of the fit of the movement's organizational structure with its substantive mission and official aims. To this end, we explain the emergence and stellar rise of the movement, compare the particularly successful nation-wide organizations of ATTAC in France and Germany, and examine the movement's transnational activities. We find ATTAC to be coherent in terms of agenda as well as organizational practices and to make a laudable effort to reflect its agenda of democratic empowerment in its political praxis. Acknowledging the enormous challenges faced by transnational civic opposition, we nonetheless conclude optimistically that ATTAC has the potential of serving as a core movement around which such opposition might usefully rally. As a subordinate contribution, our investigation poses the question of how to most usefully conceptualize the nature and role of the movement. We invite scholarly dialogue by locating ATTAC in the context of the study of social movements and transnational civil society and by enriching the theoretical debate on the nature of the emerging global opposition with our empirical observations on one of its main protagonists. Annette Freyberg-Inan is assistant professor at the Political Science Department of the University of Amsterdam. She specializes in the areas of International Relations Theory; International Political Economy and Globalization; European Integration, Democratization and Enlargement; Romanian Politics; Political Psychology; and Methodology. Her most recent publications includeWhat Moves Man: The Realist Theory of International Relations and Its Judgment of Human Nature(New York: SUNY Press, 2004); ‘Organic intellectuals and counter-hegemonic politics in the age of globalisation: the case of ATTAC’, with Vicki Birchfield, in Catherine Eschle and Bice Maiguashca (eds), Critical Theories, World Politics and the ‘Anti-Globalization Movement’(London: Routledge, forthcoming 2005); ‘Transition economies’, in Richard Stubbs and Geoffrey Underhill (eds), Political Economy and the Changing Global Order(Oxford University Press, 3rd ed., forthcoming 2005); Transition, Civil Society, and the Social Sciences in Romania(Stuttgart/Hannover: Ibidem Verlag, forthcoming 2005); ‘World system theory: how the fate of Kosovo reflects the logic and the grip of the world capitalist order’ in Jennifer Sterling-Folker (ed.), Making Sense of IR Theory(Boulder, CO: Lynn Rienner, forthcoming 2005); ‘Which way to progress? The impact of international organizations in Romania’, in Ronald Linden (ed.), Norms and Nannies: The Impact of International Organizations on the Central and East European States(Lanham, MD: Rowman & Littlefield, 2002). Vicki Birchfield is an assistant professor in the School of International Affairs at the Georgia Institute of Technology. Her research interests include comparative and international political economy and European politics. She is currently completing a book manuscript entitledInstitutions, Values and Income Inequality in Capitalist Democraciesand has published articles in theReview of International Political Economy, European Journal of Political Researchand theReview of International Studies.
Political Science
Keywords: ATTAC; globalization; international studies; neoliberalism; social movements

The Continuing 'Wind of Change' in the Balkans: Sources of Housing Inequality in Bulgaria - Vesselinov, Elena (Urban Studies (Routledge), 2004)
The research in this paper explores the institutional changes in the housing system during the period of market transition in Bulgaria, which follow suit with the greater societal transformations. The societal changes are linked theoretically with Polanyi's understanding of the transition from a non-market to a market society. His argument helps in establishing the institutional context of the macroeconomic changes in the past decade. The article then focuses on the changing sources of housing inequality. It is argued that there are two urban regimes of housing inequality: the regime of controlled uniformity during the period of socialism and the regime of primitive diversity during the period of market transition. The two regimes are produced mainly through the changing role of the state.
Sociology; Urban Studies
Keywords: Bulgaria; cities & towns; equality; housing; macroeconomics; socialism; urban studies

Meat for the Multitudes: Market Culture in Paris, New York City, and Mexico City over the Long Nineteenth Century - Horowitz, Roger; Pilcher, Jeffrey M.; Watts, Sydney (American Historical Review, 2004)
Examines an earlier period of oscillation between state intervention and market liberalization in the meat trades of Paris, France New York City, and Mexico City, Mexico. Explanation on market culture; Argument of economic historian Karl Polanyi on the modern capitalist system and market rationality; Discussion on the rules governing the relationship between civil society and state power in the meat trade.
History
Keywords: Mexico; Mexico City; New York; Paris (France); civil society; intervention (federal government); liberalism; market liberalization; meat industry; state intervention

Rules of Privatization: Contradictions in Neoliberal Regulation of North Pacific Fisheries - Mansfield, Becky (Annals of the Association of American Geographers, 2004)
Recent changes in fisheries regulation in the U.S. North Pacific reveal how neoliberalism is constituted in practice, and the forms that neoliberalism takes when it engages with environmental management and ecological processes. Whereas neoliberalism can be taken as a political economic philosophy that posits that markets, without state involvement, can best allocate resources, the history and practice of neoliberalism show that it is not as unified as it often appears. Analysis of contemporary fisheries policy reveals not only contradictions in neoliberal approaches, but also how those contradictions are shaped by the environmental context of the industry. This article discusses the rationale for neoliberalism in fisheries and the governance changes enacted in the 1998 American Fisheries Act, which privatized the fishery for Alaska pollock by closing the fishery to all new entrants, providing a set percentage of the yearly catch to “cooperatives” of participants, and allowing individuals to lease their shares. Karl Polanyi's notion of the “double movement” provides a framework to argue that even though regulators tout these reforms because they rely on market mechanisms to resolve recalcitrant ecological and economic problems in these fisheries, writing and implementing the act simultaneously involved complex rule making designed to protect the market. This form of neoliberalism results from the history of fisheries regulation, including recent emphasis on cooperative management, and the ecological characteristics of marine fish. Moves to privatize the oceans entail developing distinctive forms of neoliberal practice that uniquely combine private industry and government regulation. Because fish are one of the last great resource commons, neoliberal approaches to fisheries mark a profound geographical transformation in the political economy of the oceans.
Geography
Keywords: Pacific Ocean; double movement; fishery policy; neoliberalism; privatization

Globalization, Labor and the 'Polanyi Problem' - Munck, Ronaldo (Labor History, 2004)
This article outlines what the Polanyi problem consists of and provides information on some of the implications that arise in developing a Gramscian/Polanyian strategy of counter-hegemony for the labor and the modern social movements, as of August 2004. Labor and new social movements are allegedly an integral element for a progressive solution of the so-called Polanyi problem, which is how the tendency towards the creation of a global free-market economy can be reconciled with a degree of stability and cohesion in society. Taking a Polanyian perspective allows the development of a historical perspective on the dual transformations of globalization and labor. Towards the end of the Second World War, Karl Polanyi wrote of how a self-regulating market that allegedly could not exist for any length of time without annihilating the human and natural substance of society. Such a utopia would allegedly destroy humanity and transform the world into a wilderness, an opinion mirrored by modern eco-socialists. The strategy and ideology of globalization as transformative revolution seems to echo and confirm Polanyi's account of the 19th century industrial revolution, an attempt to set up a self-regulating market.
Sociology; Political Science
Keywords: GRAMSCI; Antonio; 1891-1937; Polanyi and Gramsci; Polanyi problem; counter-hegemony; economic policy; free enterprise; globalization; international relations; labor movement; labour movement; social movements

Dynamics of Conflict and System Change: The Great Transformation Revisited - Halperin, Sandra (European Journal of International Relations, 2004)
Karl Polanyi's analysis in The Great Transformation has played a prominent role in shaping our understanding of the nature and outcome of both globalization and the movements that have emerged to resist it. However, this article argues that Polanyi's account of the rise and demise of Europe's 19th-century market system is, in important respects, incomplete and misleading. Its central concern is Polanyi's neglect of class structures and processes and how this leads him to mischaracterize both the international and domestic institutions of Europe's 19th-century market system, and the central dynamic driving its development and ultimate collapse. The article critically reviews key features of Polanyi's analysis. Based on this review, it then presents a re-reading of the history of Europe's unregulated market system. Finally, it considers the implications of this alternative account for how we view the context and conditions for globalization and the ways it can best be resisted or shaped in less destructive ways.
Political Science; International Relations
Keywords: Europe; class conflict; globalization; international relations; international trade; markets; organizations and policy; social conflict; transformation; transnational capital

And if there was no state?: critical reflections on Bates, Polanyi and Evans on the role of the state in promoting development - Menocal, Alina Rocha (Third World Quarterly, 2004)
The article review three books about the role of the state in promoting development. It includes "Markets and States in Tropical Africa: The Political Basis of Agricultural Policies," by Robert Bates, "Embedded Autonomy: States and Industrial Transformation," by Peter Evans and "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
Political Science; Development Studies
Keywords: BATES; Robert H.; 1942-; EVANS; Peter; 1944-; Embedded Autonomy: States and Industrial Transformation; Great Transformation; The (Book); Markets & States in Tropical Africa: The Political Basis of Agricultural Policies (Book); nonfiction; state development

Agenda 2010: German social democracy and the market state - Thompson, Peter (Debatte, 2004)
Ideology is always for something. Who thought neoliberalism was any different? The post-Cold War provides an excellent laboratory in which to observe 20th c. civilization crumbling, even as it marches towards world markets unbounded by law or social principles. Through repetition and rhetorical sleight-of-hand, the market has robbed the state and thus the polis of its agency. Thus, Schroeder’s SPD is contemplating yet another retreat from the social democratic model, in favor of the post-welfare-state model already well established in the UK and America. And yet within the SPD ranks are breaking as members watch the party abdicate Germany’s basic social contract. These events are reminiscent of M. Polanyi’s The Great Transformation [1744], and they demonstrate once again Marx’s prescience.
Political Science; Germanic Studies
Keywords: Germany; Great Transformation; The (Book); Social Democratic party; markets; social democracy

The third way and the third world: poverty reduction and social inclusion in the rise of 'inclusive' liberalism - Porter, Doug; Craig, David (Review of International Political Economy, 2004)
In the wake of frank neo-liberalism, and in the context of rising security fears, ways are being found to provide market liberalism with a more inclusive face. The Poverty Reduction Strategies currently prominent in international development, and Thirdway OECD 'Social Inclusion' policy frames claim common purpose to promote 'opportunity, empowerment and security' for people and places on the peripheries of global economies and societies. They share commitments to global economic integration and openness, market led growth, 'good' and 'joined up' governance, local and social partnerships, and wide-ranging activation of 'capacities'. But the high rhetorical aspirations of liberalism to social 'inclusivity' have so far overreached empirical gains for the poor. Drawing on developing country examples of Poverty Reduction Strategy and public policy in New Zealand's current Labour government, this paper sketches salient features of 'inclusive' liberalism. It critically examines its status as a Polanyian turn within a wider liberal project, which seeks to re-embed and legitimate a liberal social and economic order.
Sociology; Political Science
Keywords: New Zealand; developing countries; international competition; international political economy; liberalism; political planning; poverty; poverty reduction; self-efficacy; social inclusion; third way

'Spatial' relationships? Towards a reconceptualization of embeddedness - Hess, Martin (Progress in Human Geography, 2004)
The concept of embeddedness has gained much prominence in economic geography over the last decade, as much work has been done on the social and organizational foundations of economic activities and regional development. Unlike the original conceptualizations, however, embeddedness is mostly conceived of as a 'spatial' concept related to the local and regional levels of analysis. By revisiting the early literature on embeddedness - in particular the seminal work of Karl Polanyi and Mark Granovetter - and critically engaging with what I will call an 'overterritorialized' concept, a different view on the fundamental categories of embeddedness is proposed. This reconceptualization then is illustrated using the poststructuralist metaphor of a rhizome to interpret the notion of embeddedness and its applicability to different geographical scales.
Geography
Keywords: GRANOVETTER; Mark; associations; cosmography; economic geography; embeddedness; geography; global production networks; institutions; new regionalism; organization; rhizome; social networks; socioeconomics

Student Labor and Evolution of Education - Sidorkin, Alexander M. (World Futures: The Journal of General Evolution, 2004)
The evolution of teaching is examined in three stages: apprenticeship, classical schooling, and mass schooling. All three stages use different social technologies to operate. The mass schooling is analyzed from the point of view of economic anthropology developed by Karl Polanyi, as a non-market economic system. Mass schooling uses the forms of motivation found in archaic, tribal economies: students do their homework and attend school out of considerations of reciprocity. Schools must be treated differently with respect to their improvement. School improvement should be based on perfecting existing non-market economic mechanisms, not on plunging schools into market economy.
Anthropology
Keywords: POLANYI; Karl; 1886-1964; apprenticeship programs; economic anthropology; education; educational anthropology; evolution of education; motivation in education

Endogenous Preferences and Embeddedness: A Reappraisal of Karl Polanyi - Rodrigues, João (Journal of Economic Issues (Association for Evolutionary Economics), 2004)
This article examines the relevance of the Karl Polanyi's contributions to economics in general and to the issue of endogeneity of human preferences in particular. Although Polanyi never spoke of endogenous preferences, one can capture in his work a vision of the historical specificity and institutional dependence of human purposes and reasons for behavior. It is undeniable that in Polanyi there is a certain tendency to overlook human volition and to fall into a kind of institutional determinism. Nevertheless Polanyi recognizes the scope for deliberate human action when he defines institutions as the embodiments of human meaning and purposes. Furthermore, in Polanyi's work, there is a very clear awareness of the complexity of the motives for human action and a defense, which is continuously reaffirmed, of the plurality of reasons to act in economic interactions and their relation to the patterns of interaction that are dominant. Nevertheless, there is a lack of a clear and well-systematized account of the possible causal links by which institutions influence human preferences. His substantive economy takes morality into account, in the sense that its foundations lie on the recognition that man is a moral being with duties toward himself and others, with an understanding of what is good and what is bad and that these moral codes exert a powerful influence upon economic affairs.
Economics
Keywords: economic anthropology; embeddedness; endogenous preferences; ethics; human behavior; institutional economics; social sciences

Third Worldism and the lineages of global fascism: the regrouping of the global South in the neoliberal era - Patel, Rajeev; McMichael, Philip (Third World Quarterly, 2004)
We come to an analysis of Third Worldism through an historical understanding of the development project, one that locates Third Worldism as a moment in a broader series of resistances both to capital and colonialism, and to the techniques used by the state to maintain hegemony. Viewing Third Worldism in this wider context, we argue, enables us to not only explain the failure of Third Worldism to deliver on its vision of emancipation from colonialism, but to also explain the shape of contemporary resistance to the world capitalist order. We argue that the theory and practice of development depends on a certain biopolitics, rooted in a regime of sovereign state control, and designed to mobilise citizens in ways favourable to capital. We hold that Third Worldism embraced this form of sovereignty and its biopolitics. Further, by blending cultural studies analysis with a Polanyian interpretation of the rise of fascism, we argue that Third Worldism can be situated as a moment in the maturation of 'global fascism'. Finally, we argue that contemporary resistances to neoliberalism have recognised the complicity of the state with capital. These 'new internationalisms' arise from the ashes of Third Worldism, with an altered understanding of 'sovereignty' that challenges the trajectory of the Third World sovereign state.
Sociology; Development Studies
Keywords: biopolitics (sociobiology); capitalism; colonies; fascism; global capital; global fascism; hegemony; liberty; sovereignty (political science)

Social Exclusion in a Comparative Context - Reimer, Bill (Sociologia Ruralis, 2004)
This paper outlines a framework for understanding social exclusion that is multidimensional, dynamic, multi-leveled, and relational. Inspired by Polanyi's classification of the modes of economic inclusion, we propose that social inclusion and exclusion processes are rooted in four types of social relations: market (exchange and barter), bureaucratic (rational-legal), associative (common interest), and communal (complex reciprocity and shared identity). Each type reflects different, but integrated processes of social exclusion and inclusion. These four types are outlined conceptually, then operationalized using data from a Canadian survey conducted in 1995 rural households. The results show the extent to which the four types of relations are used for social support, their interdependence, and their relationship to selected household characteristics and outcomes. The policy implications discussed emphasize the ways in which building capacity in all four types of relations can increase the level of social inclusion.
Sociology
Keywords: Canada; economic inclusion; rural sociology; social exclusion

Debt Abides: A Prolegomena for Any Future Chapter 11 - Ayer, John D. (American Bankruptcy Law Journal, 2004)
This article presents information related to market transactions. As a mode of organization, markets are so pervasive in our own lives that it may be hard to think just how novel and contingent (in geologic time) they may be. It was economist Karl Polanyi who sought to isolate a juncture in this process of "becoming a market", the point at which the idea of the market transaction becomes not just a tool or an instrument, but a central organizing principle of social life. But it is not clear that even Polanyi would have been able to conceive a later stage, a stage in which the market becomes not merely a tool of the firm or an expression of sovereignty, but a substitute for the firm and for sovereignty itself.
Law; Political Science
Keywords: autonomy (Political science); international law; markets; organization; political science; social interaction

The Great Transformation in Understanding Polanyi: Reply to Hejeebu and McCloskey - Blyth, Mark (Critical Review, 2004)
Santhi Hejeebu and Deirdre McCloskey's rebuttal to Karl Polanyi's Great Transformation begs several important questions. Yes, commerce can be found throughout human history–but is that the same as saying that people have been equally capitalistic at all times? If not, then how did modern capitalism come into being? Hejeebu and McCloskey portray capitalism as having evolved gradually, indeed quite naturally, rather than being a contingent product of politics. Not inconsistently, Hejeebu and McCloskey radically distinguish between what people "think" and what they "do"–that is, between their ideas and their actions. This distinction, too, suggests that human action is ahistorically capitalistic–whatever human agents at different times and places might think.
Political Science
Keywords: Hejeebu; McCloskey; economic thought; history; modern capitalism

Pinochet meets Polanyi? The Curious Case of the Chilean Embrace of "Free" Market Economics - Cypher, Jame M. (Journal of Economic Issues, 2004)
This article argues, within the context of Karl Polanyi's work, that the common view of Chile is doubly miscontrued, in terms of free market economics. Events since the end of the dictatorship (1989) tend to confirm Polanyi's hypothesis in 'The Great Transformation' (1957; discussed in the following section) while at the same time negating the Chicago School's view that a free market society could be built–even under a dictatorship. In Chile from September 1973 onward through 1989, the Chicago School–inspired economists known as the Chicago Boys, engaged in what would appear to be the most determined utopian endeavor of economic liberalism to set up a self-regulating market system. It is the hypothesis of this paper that the Chicago School failed spectacularly in this effort and that the credit they have widely received for successfully remaking the Chilean economy properly belongs to the antithesis of the Chicago School–successful state-led efforts to restructure the economy and foster development. Far from the fictitious utopia of the free market, under the dictatorship the state was also heavily involved in projects designed to massively transfer economic rents to the private sector. Consistent with Polanyi's thesis, the Chicago School was able to drastically reduce Chile's social legislation, labor legislation, and social controls over the exploitation of the natural resources of Chile only within the context of a military dictatorship. While Chile's elected governments have embraced the Chicago School's faith in unlimited and unregulated free international trade, in the area of social legislation and labor legislation there are very strong indications that civil society is systematically and effectively striving to overcome the retrograde steps imposed by the dictatorship.
Economics
Keywords: Chicago school of economics; Chile; economic conditions; economics; free enterprise; politics and government

Heilbroner and Polanyi: A Shared Vision - Dimand, Robert W. (Social Research, 2004)
The article presents the shared vision of Polanyi and Heilbroner. This paper focuses on the parallel ideas of economists Karl Polanyi and Robert Heilbroner. Their concept on the role of market system in the emergence of economics as a field of study is explained. More issues included are the requirements for the transformation of a pre-market society into a true market, Polanyi's influence to several economists, and relevance of the Polanyi/Heilbroner vision of the market system to the postcommunist countries transition to the market.
Economics
Keywords: HEILBRONER; Robert; economics; economics - statistical methods; economists; markets; social sciences; societies; statistics

Re-Inventing Karl Polanyi: On the Contradictory Interpretations of Social Protectionism - Drahokoupil, Jan (Sociologický Časopis / Czech Sociological Review, 2004)
The ideas of Karl Polanyi's The Great Transformation have often been referred to in the recent debates that have emerged as a reaction to the rise of neoliberal policies. This paper deals with contradictory interpretations of the notion of social protectionism in the work of Karl Polanyi. There are two opposing interpretations distinguished here. The first interprets social protectionism as a balancing principle of economic liberalism. The second understands social protectionism as a part of market pathology. In order to assess the validity of competing interpretations, the author puts forth an account of social protectionism in the context of Polanyi's theory of the economy and society. The author concludes that the popular notion of social protectionism as a balancing principle of economic liberalism does not correspond to Polanyi's theory. In addition, the author offers a skeptical commentary on the utility of Polanyi for understanding social protectionism in social analysis.
Sociology; Economics
Keywords: critique; social protectionism

Polanyi and the History of Capitalism: Rejoinder to Blyth - Hejeebu, Santhi; McCloskey, Deirdre (Critical Review, 2004)
Mark Blyth's rebuttal to our constructive critique of Polanyi "blithely" takes for granted the accuracy of Polanyi's now-outdated historiography of capitalism–by means of a loose, overly expansive definition of capitalism that question-beggingly equates it with modernity. Blyth emphasizes the need to view markets as "socially embedded," with which we agree–but he appears not to take account of the individual self-interest that is thus embedded. Similarly, he asserts a priori the role of ideas in history, in parallel to the economists he condemns (unfairly) for reading ideas out of history a priori. All of this poorly serves the cause of extracting Polanyi's welcome emphasis on social embeddedness and on the empirical from the ideological and methodological certitudes and errors in which The Great Transformation placed them.
Economics
Keywords: BLYTH; Mark; history of economic thought: individuals

Polanyi Symposium: a conversation on embeddedness - Krippner, Greta; Granovetter, Mark; Block, Fred; Biggart, Nicole; Beamish, Tom; Hsing, Youtien; Hart, Gillian; Arrighi, Giovanni; Mendell, Margie; Hall, John; Burawoy, Michael; Vogel, Steve; et al. (Socio-Economic Review (2004), 2004)
This conversation, transcribed from a conference in April 2002, is intended to illuminate current debates about the use and abuse of the embeddedness concept in economic sociology.
Sociology
Keywords: economic sociology; embeddedness; markets; symposium

Karl Polanyi o la humildad de las ciencias sociales - Rendueles, César (NEXO. Revista de Filosofía, 2004)
EN: This essay proposes a periodization of Karl Polanyi’s work, from his early writings in Vienna to his anthropological work developed in the context of the substantivist-formalist discussion. The outstanding feature of this studies is the way they combine empirical sharpness with epistemological modesty. Unlike orthodox economy and imperialism theories, Polanyi doesn’t ignore the precarious theoretical situation of social science. His investigations are based on empirical thesis both broadly accepted and heuristically productive. Este artículo analiza las distintas fases de la obra de Karl Polanyi, desde sus pri- meros escritos en Viena a su obra antropológica en el contexto del debate entre sus- tativistas y formalistas. La principal virtud de estos estudios es su mezcla de acier- to empírico y modestia epistemológica. A diferencia de la economía ortodoxa o de las teorías del imperialismo, Polanyi no rehuye la precaria situación teórica de las ciencias sociales. Sus investigaciones se basan en tesis empíricas ampliamente aceptadas que, sin embargo, demuestran una notable vitalidad heurística.
Sociology
Keywords: Karl Polanyi; epistemology; periodization; social science